Surgical correction of tetralogy of Fallot: general dominant world practice and current trends - Borodinova, O. (Ukrainian Journal of Cardiovascular Surgery, 2017)
The first successful correction of Tetralogy of Fallot was done in August 31, 1954 by surgeons C. W. Lillehei and R. L. Varco. Since that time the problem of its correction is under constant development and improvement due to the ab-sence of an ideal solution. The purpose of the paper – to review different methods of Tetralogy of Fallot surgical correction from literature, their advantages, disadvantages and to determine the optimal technique of Tetralogy of Fallot correction. Results and discussions. Correction of the tetralogy of Fallot with transventricular closure of the ventricular septum de-fect, ventriculotomy and transannular plasty still remains the method of choice in most centers. This is due to several factors. For the first, methods with transatrial/transpulmonary closure of the ventricular septum defect and minimal transanular plasty or with preservation of the pulmonary artery valve are characterized by an increased complexity of intraoperative technique and a dificulty in the training of specialists. Secondly, these patients are expected to have a more severe periopera-tive period and a potentially high risk of reoperations due to residual obstruction of the right ventricular outflow tract. Thus, method of ToF repair is mostly a personal surgeon’s choice guided by his own experiences, feelings and measurements of cardiac structures on a cardioplegic heart. Conclusion. Different methods of surgical correction of Tetralogy of Fallot, their advantages, disadvantages, immediate and long-term results have been presented on the literature basis. According to this information, the traditional method of surgical correction of Tetralogy of Fallot is transventricular closure of ventricular septal defect with expanded ventriculotomy and transannular plasty, despite the high risk of sudden death and the need of pulmonary artery valve implantation in a re-mote period. Correction of Tetralogy of Fallot with transatrial/transpulmonary ventricular septal defect closure and minimal transannular plasty or preservation of the pulmonary artery valve have performed better survival and less risk of reinterven-tions on the outflow tract of the right ventricle. However, the question of feasibility, efficacy and safety of this technique re-mains controversial due to the lack of echocardiographic and intraoperative quality and safety control criteria for performed correction and long-term follow-up data.